The Public’s Perception of the Operating Standards of the Jamaica Defence Force (JDF): A Quantitative Inquiry - Paul Andrew Bourne; Caroline McLean; Vincent M.S. Peterkin; James Fallah; Clifton Foster (Ridwan Institute, 2023)
Introduction: The Jamaica Defence Force (JDF), a military organization, collaborates with the Jamaica Constabulary Force (JCF) to police society. The widespread and frequent engagement of the JDF in a paramilitary role results in regular interaction with the public. No existing studies in the current literature have examined the public’s perception of the operating standards of the JDF. Objective: This study seeks to evaluate and explore the JDF from an operational standpoint. The Operations Management Theory (OMT) is used to examine whether the public’s perception of the operating standards of the JDF has changed in the last decade (2012 -2022). Methods and materials: This research employed a national cross-sectional web-based descriptive research design. Data collection occurred from July 13, 2022, to August 11, 2022. Using the 2019 population of Jamaica obtained from the Statistical Institute of Jamaica, with a 3.4% margin of error and 95% confidence interval, the calculated sample size is 831 resident Jamaicans. The response rate was 82.1% (n=762). Findings: The majority of the sampled respondents were Jamaicans (97.1%, n=766), resided in Jamaica (88.9%, n=700), females (59.6%, n=472), and resided in Manchester (19.2%, 150). Of the Jamaicans (n=764), 89.3% (n=682) of them reside in Jamaica compared to 10.7% (n=82) reside outside. Furthermore, 89.3% of Jamaicans resided in Jamaica compared to 77.3% of non-Jamaicans (?2 (1) = 3.125, P = 0.077). The findings indicate that people have lost respect for the JDF in the last 6 months. Discussion: The people’s perception of the operating standards of the JDF will provide an understanding of crime management challenges in Jamaica. Combined with effective management and implementation of strategies to meet the intended mission and vision, the JDF should consider image rebranding to address the decline in public perception and trust. Conclusion: Despite the traditional military structure of the Jamaica Defence Force, the organization has been deployed on the streets of Jamaica by political administrations to curb and remedy the difficulty of policing society, and this explains a justification for a public assessment of this organization. The public is indecisive on whether the Jamaica Defence Force is too frequently used jointly with the Police Constabulary Force to police the streets of Jamaica as well as being neutral on the overall operating standards of the organization.